Peningkatan Hasil Belajar Materi Berbagai Kelompok Sosial Masyarakat Melalui Media Gambar Siswa Kelas V SDN Banyuajuh 5 - Bayu Sabilha Naufal; Agung Setyawan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
If the learning media used is not in accordance with the concepts and activities required, then learning activities and student achievement can decrease. Therefore, one solution is to use appropriate learning media. This study aims to: (1) improve the learning outcomes of social group material through the use of media images in fifth grade students at SDN Banyuajuh 5, and (2) assess the effectiveness of media images on student learning outcomes. The subjects of this study were fifth grade students at SDN Banyuajuh 5, Bangkalan Regency, with a total of 12 students consisting of 7 male students and 5 female students. This study uses a type of classroom action research with data collection techniques through interviews, observation, and test evaluation. The results showed that there was an increase in the percentage of successful learning outcomes in cycle I by 50% and increased to 87% in cycle II. From these results it can be concluded that the use of media images can improve learning outcomes of social group material effectively.